The Inaccuracy of Sample-Based Confidence Intervals to Estimate A Priori Ones - David Trafimow; Joshua Uhalt (Methodology, 2020)
Confidence intervals (CIs) constitute the most popular alternative to widely criticized null hypothesis significance tests. CIs provide more information than significance tests and lend themselves well to visual displays. Although CIs are no better than significance tests when used solely as significance tests, researchers need not limit themselves to this use of CIs. Rather, CIs can be used to estimate the precision of the data, and it is the precision argument that may set CIs in a superior position to significance tests. We tested two versions of the precision argument by performing computer simulations to test how well sample-based CIs estimate a priori CIs. One version pertains to precision of width whereas the other version pertains to precision of location. Using both versions, sample-based CIs poorly estimate a priori CIs at typical sample sizes and perform better as sample sizes increase.